2011
DOI: 10.1186/1471-2377-11-118
|View full text |Cite
|
Sign up to set email alerts
|

Gender-dependence of substituted judgment on quality of life in patients with dementia

Abstract: BackgroundSubstituted judgment asks the proxy to decide what the patient would have decided, had he or she been competent. It is unclear whether substituted judgment of the patient's quality of life can serve as a surrogate measure in patients with dementia.Methods212 patients with dementia and their proxies were interviewed in their homes. Dementia syndrome was characterized with cognitive, non-cognitive and functional scales. Quality of life (QoL) was assessed with the QoL-AD.ResultsSubstituted judgment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…16 When it comes to evaluating the patient's quality of life (QoL-p), both burden [17][18][19][20][21][22] and depression [19][20][21][22][23][24] in caregivers have been shown to produce a negative bias in their assessments. Likewise, burden and poor mental health in caregivers are inversely correlated with their perception of QoL-p 25,26 ; female caregivers give the most negative ratings of QoL-p, 17,27 and they also present with more depression and anxiety. 28,29 In light of the above, the aim of the present study was to identify and quantify the caregiver factors that may lead to variability in their assessments of the patient's functional capacities, neuropsychiatric symptoms, anosognosia, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 When it comes to evaluating the patient's quality of life (QoL-p), both burden [17][18][19][20][21][22] and depression [19][20][21][22][23][24] in caregivers have been shown to produce a negative bias in their assessments. Likewise, burden and poor mental health in caregivers are inversely correlated with their perception of QoL-p 25,26 ; female caregivers give the most negative ratings of QoL-p, 17,27 and they also present with more depression and anxiety. 28,29 In light of the above, the aim of the present study was to identify and quantify the caregiver factors that may lead to variability in their assessments of the patient's functional capacities, neuropsychiatric symptoms, anosognosia, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous research, which has found greater burden and more psychiatric symptoms among female caregivers, 28,29,[43][44][45] who also gave more negative assessments of the patient's neuropsychiatric symptoms 7 and quality of life. 17,27 These gender differences could be due to men paying less attention to their emotions or to women using less effective coping strategies. 46 At all events, the present data also indicate that women have a greater involvement in caregiving tasks.…”
Section: Influence Of Caregiver Factors On Patient Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among caregivers, poorer ratings of QoLp have been shown to be associated with functional deficits (10,11) and behavioral disorders (3,9) in the patient and with burden (3) and depression (12,13) in the caregiver. Some authors have also reported that perceptions of QoLp are affected by sociodemographic and contextual factors such as the caregiver's gender (14), his or her relationship to the patient, (15)(16)(17)) the patient's place of residence (2,3) or the environmental conditions. (18) Although the assessment of QoLp may be a valid and reliable indicator at any stage of the disease there are certain aspects which require careful consideration.…”
mentioning
confidence: 99%
“…(18) Although the assessment of QoLp may be a valid and reliable indicator at any stage of the disease there are certain aspects which require careful consideration. One of the most important in this regard concerns the large discrepancy between patient and caregiver reports of quality of life, (3,19) this being particularly notable as the severity of dementia increases; (12)(13)(14)(15)(16)(17)(18)(19)(20) other factors to consider in this regard are the influence of depression (21) and reduced awareness of deficits (anosognosia) in the patient. (22)(23)(24)(25)(26) In light of the above the aims of the present study were as follows: 1) to determine the influence of severity of dementia, depression and anosognosia as regards the discrepancies between patient and caregiver reports of QoLp; and 2) to identify specific groups of patients associated with these discrepancies.…”
mentioning
confidence: 99%